(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Lysozyme hydrochloride, derived from Hen Egg Lysozyme, is one of classical anti-airway inflammatory drugs. It has been widely administered in Japan, but its molecular potential is unknown. To confirm this classical drug as anti-inflammatory agent, pro-inflammatory cytokines in Epithelial Cells infected by RSV with lysozyme hydrochloride were measured. Lysozyme hydrochloride suppressed the production of IL-6, IL-1β, G-CSF although IL-8 and IFN-γ was not changed. Lysozyme hydrochloride inhibits pro-inflammatory cytokines in Epithelial cells infected with Respiratory Syncytial Virus, and may affect to airway inflammation.